Effect of cocoa (Theobroma cacao L.) on platelet function testing profiles in patients with coronary artery disease: ECLAIR pilot study. Issue 2 (13th September 2022) - Seecheran, Naveen Anand; Sukha, Darin; Grimaldos, Kathryn; Grimaldos, Gabriella; Richard, Srivane; Ishmael, Aleena; Gomes, Ceylon; Kampradi, Lirmala; Seecheran, Rajeev; Seecheran, Valmiki; Peram, Lakshmipathi; Dookeeram, Darren; et al.
Abstract : Introduction: This prospective pharmacodynamic nutraceutical study assessed the effect of a 1-week trial of 30 g/day of 65% cocoa (dark chocolate) ( Theobroma cacao L.) consumption intervention on platelet reactivity. Methods: Patients with stable coronary artery disease (CAD) (n=20) who were on maintenance dual antiplatelet therapy of aspirin (ASA) 81 mg/day and clopidogrel 75 mg/day were recruited. Platelet function was evaluated with the VerifyNow P2Y12 reaction unit (PRU) and aspirin reaction unit (ARU) assays (Werfen, Bedford, Massachusetts, USA) and assessed prior to initiation of and after a 1-week trial of 30 g/day of 65% cocoa consumption intervention. Results were compared with a paired t-test. Results: Cocoa augmented the inhibitory effect of clopidogrel, demonstrated by a reduction of 11.9% (95% CI 5.7% to 18.0%, p value 0.001), significantly decreasing the PRU by 26.85 (95% CI 12.22 to 41.48, p value 0.001). The inhibitory effect of ASA was not impacted by cocoa, reflected by a non-significant reduction in ARU of 17.65 (95% CI 21.00 to 56.3, p value 0.351). No patients experienced any serious adverse events. Conclusions: Cocoa augmented the inhibitory effect of clopidogrel but not ASA. This nutraceutical study could be potentially informative and applicable for patients with stable CAD. Further long-term studies are required to confirm these exploratory findings. Trial registration number: NCT04554901 .